Student conceptual and epistemic quality improvement argumenation with scaffolding on argument-driven inquiry - Neni Hasnunidah; Herawati Susilo; Mimien H. Irawati; Hadi Suwono (Universitas Negeri Yogyakarta, 2022)
This study is aimed at comparing the quality of students’ argumentation based on conceptual and epistemic aspects between learnings that implement argument-driven inquiry (ADI) and argument-driven inquiry with scaffolding (ADIS) models. The data were collected through dialogic argumentation observation sheets for the students and audio-visual recordings and were analyzed qualitatively. The study invoved 67 participants in the ADI group and 81 participants in the ADIS group. The quality of student argument with the ADI model differed significantly from the ADIS model. Results show that the students in the ADIS class were are better at providing sufficient data to support claims and coherent causal explanations to explain a certain phenomenon, and at organizing accurate rhetorical references when expressing data.